2019
DOI: 10.3390/genes10040316
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Dynamics of Double Recessive Mutant, o2o2o16o16, Reveals the Transcriptional Mechanisms in the Increase of Its Lysine and Tryptophan Content in Maize

Abstract: In maize, pyramiding of o2 and o16 alleles can greatly improve the nutritional quality of grains. To dissect its molecular mechanism, we created a double recessive mutant line, o2o2o16o16, by introgression of the o2 and o16 alleles into the wild-type maize inbred line, by molecular marker-assisted backcross selection. The kernels (18 day after pollination (DAP), 28 DAP, and 38 DAP) of the o2o2o16o16 mutant and its parent lines were subject to RNA sequencing (RNA-Seq). The RNA-Seq analysis revealed that 59 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…Similar findings were found during the regulation of methionine metabolism (Song et al, 2013). Interestingly, high tryptophan levels were found to be associated with high-lysine plants (Yang et al, 2018;Wang et al, 2019), while Yang et al (2018) revealed that the accumulation of lysine induced the tryptophan synthesis and metabolism in high free lysine transgenic rice (Oryza sativa L.). However, few reports have documented the relationship between metabolism of different amino acid families, highlighting the need for further research.…”
Section: Metabolic Flux Of Amino Acids In Plantssupporting
confidence: 69%
“…Similar findings were found during the regulation of methionine metabolism (Song et al, 2013). Interestingly, high tryptophan levels were found to be associated with high-lysine plants (Yang et al, 2018;Wang et al, 2019), while Yang et al (2018) revealed that the accumulation of lysine induced the tryptophan synthesis and metabolism in high free lysine transgenic rice (Oryza sativa L.). However, few reports have documented the relationship between metabolism of different amino acid families, highlighting the need for further research.…”
Section: Metabolic Flux Of Amino Acids In Plantssupporting
confidence: 69%
“…The kernels of double recessive mutant o2o2o16o16 contained increased Gly as well as reduced Glu and Met. Coincidently, a total of 24 folate-related genes showed significant variation of expression between mutant and wild type, and 21 of them were also found in our WGCNA module analysis, including the key folate genes ADCS, DHNA2, GGH, SHMT7-1, SHMT7-2, and GCST (Tables S3 and S7) [68]. Similarly, studies in tomato and millet (Setaria italica) also demonstrated that folate accumulation in different cultivars was closely related to the genes involved in pteridine branch, ρ-ABA branch, folate degradation, and serine/THF/5-M-THF cycle, such as SiDHNA2, SiGGH, SiSHMT2, SiSHMT3, SiMTHFR, SiAMT (known as GCST), SlDHNA, and SlADCS [25,69].…”
Section: Discussionmentioning
confidence: 70%
“…Similar connections were also identified between amino acid and folate metabolisms. For instance, O2 and O16 encode the transcription factors of the basic leucine zipper family, and they have been used to improve the amino acid quality of maize grains [68]. The kernels of double recessive mutant o2o2o16o16 contained increased Gly as well as reduced Glu and Met.…”
Section: Discussionmentioning
confidence: 99%
“…The RT-qPCR was performed using the CFX96 Touch™ Real-Time PCR Detection System (Bio-Rad, Hercules, CA, USA). The Actin gene was used as the endogenous control [54]. The relative expressions of RNAs and targets were calculated using the 2 −ΔΔCt method [55].…”
Section: Methodsmentioning
confidence: 99%